Identification of flood source areas in Pahang river basin, peninsular Malaysia. - Sulaiman, Wan Nor Azmin; Heshmatpoor, Ali; Rosli, Mohd Hafiz (Thai Society of Higher Eduction Institutes on Environment, 2010)
The roles of upland watersheds in flood source contribution towards downstream areas in a river basin system are generally neglected in the inclusion of management strategy related to downstream flood management. In this study an assessment on the flood source area of Pahang river basin was attempted. The concept of unit flood response as an index of hydrologic response was used in identifying the flood source areas for the basin. The results indicated that among the 16 sub-basins of Pahang river basin, sub-basin of Sungai Pahang is ranked first in production of flood discharge while Sungai Perting sub-basin is ranked last in term of production of flood discharge. Comparison between maximum daily discharge of upper and lower segments of Pahang river basin indicated that up-stream watershed contributes significantly high and more flood (94.78%) than down-stream (5.22%). In addition, the upland watersheds were found to more efficient in producing surface runoff and send the floodwater to the lower receiving basin of Sungai Pahang. Considering that basin flood response is generally a nonlinear function of many factors, the sub-basins that are located nearest to and most distance from the basin outlet do not necessarily generate the highest and lowest contribution to the flood peak at the outlet. Similarly, sub-basins producing the highest or lowest absolute or specific discharge at their own outlet may not necessarily ranked first and last in flood index.